A 1000-YR RECORD OF FOREST FIRE ACTIVITY FROM ECLIPSE ICEFIELD, YUKON, CANADA - Yalcin K.; Wake C.P.; Whitlow S.I.; Kreutz K.J. (My University, 2006)
A 1000-yr record of forest fire activity has been developed using three annually dated ice cores from Eclipse Icefield, Yukon, Canada. Forest fire signals were identified as NH4+ residuals above a robust spline and corroborated by an empirical orthhogonal function (EOF) analysis that identified a chemical association in the NH4+, C 2O42- and K+ records similar to that observed in forest fire plumes. These statistical techniques yielded similar records of forest fire activity, although the EOF analysis provides more conservative identification of forest fire signals. Comparison of forest fire signals in the Eclipse ice cores with the record of annual area burned in Alaska and the Yukon demonstrates that 80% of high fire years in Alaska and 79% of high fire years in the Yukon are identifiable as NH4+ concentration residuals in at least one core from Eclipse Icefield, although any individual core records 36-67% of these events. The Eclipse ice cores record high fire activity in the AD 1760s, 1780s, 1840s, 1860s, 1880s, 1890s, 1920s-1940s and 1980s. Peak fire activity occurred in the 1890s, possibly reflecting anthropogenic ignition sources associated with the large influx of people to the Yukon during the Klondike Gold Rush. Periods of low fire activity are evident during the 1770s, 1810s-1830s, 1850s, 1950s and 1960s. Extending our proxy of fire activity to AD 1000 using annual NH4+ concentrations from our one core that extends back this far provides evidence of high fire activity from 1240 to 1410 during the waning stages of the 'Mediaeval Warm Period'. © 2006 Edward Arnold (Publishers) Ltd.
Keywords: 'MEDIAEVAL WARM PERIOD'; ALASKA; CANADA; FIRE HISTORY; FOREST FIRES; ICE CORES; LATE HOLOCENE; YUKON